The ratio of the principle of ensuring the suspect, accused the right to defense with other principles of the criminal process (Journal of actual problems of jurisprudence, 2018)
The development of the principle of ensuring the suspect, accused the right to defense requires the existence of strong professional protection at all stages of the criminal process. To date, the possibility of the participation of a lawyer in criminal proceedings has been markedly expanded. The purpose of this article is to consider the principle of ensuring that the suspect, accused person has the right to defensewith other principles in the criminal process. The ability to determine whether the lawyer has sufficientfunds for the successful implementation of the defense function. Ensuring that the suspect and the accusedhave the right to defense is organically derived from the presumption of innocence of the accused:the right to defense is required only for those who have not yet been convicted and only suspectedand accused of committing a crime. The obligation to ensure the realization of the right of the suspectand the accused to defense is assigned to the state authorities conducting criminal proceedings andresponsible for its successful completion. However, the principle of competition, which is fundamentaland dominant in the current Criminal Procedure Code of the Republic of Kazakhstan, degrades, in ouropinion, its own importance and interconnection between the principles of the presumption of innocenceand ensuring the right to defense to the suspect and the accused. With the adoption of the newCriminal Procedure Code of the Republic of Kazakhstan, the extreme support of the adversarial processin the criminal process, characterized by a refusal to establish the truth, a fairly passive role of the courtin proving, actually placing the responsibility of proving on the parties », which could not but affect thevery principle of ensuring the suspect and the accused protection. This principle is depleted, as it is carriedout, in essence, only at the formal-legal level of competition and therefore is narrowly pragmatic innature, which inevitably affects the very quality of such protection. The pre-trial investigation authoritiesare obliged to unswervingly comply with all the norms relating to ensuring the rights of the accused. Eachof the violations of these norms ultimately leads to a violation of the principle of ensuring the defendant’sright to a defense and interferes with the establishment of the truth in the case.Key words: suspect, accused, defense, pretrial investigation, presumption of innocence, adversary.